Recent advances in alloy counter electrodes for dye-sensitized solar cells. A critical review. (1st October 2015) - Tang, Qunwei; Duan, Jialong; Duan, Yanyan; He, Benlin; Yu, Liangmin
Graphical abstract: Highlights: Recent advances on alloy CEs for DSSCs are reviewed. Pt-free CEs with nonmetal species suffer from structure deviation or collapse at cell operation. Alloyed CEs exhibit enhanced catalytic activity for triiodide reduction. Alloyed CEs display enhanced dissolution resistance in liquid electrolyte. Abstract: Dye-sensitized solar cell (DSSC) has been considered as a potentially cost-effective alternative to silicon solar cell. By optimizing three components of a typical DSSC including a dye-sensitized wide-bandgap semiconductor photoanode for creating and transporting electrons, n redox electrolyte, and a counter electrode (CE) for reducing oxidized species in electrolyte, a maximum power conversion efficiency of 13% has been determined. The high cost of DSSCs is to a large part dictated by the high loading of Pt required to catalyze the triiodide reduction reaction. Arguably one of the arising routes to reduce fabrication cost of DSSCs with no sacrifice of catalytic activity of CEs is to alloy Pt with other metals/nonmetals or to replace Pt with Pt-free alloys. In this perspective paper, we outline the advances of alloy CEs in comparison with other alternatives such as carbonaceous materials and conductive polymers and their hybrids including design concepts, fabrication approaches, and properties. Finally, this review launches prospects and challenges of promising alloy CEs for their applications in high-efficiency DSSCs.